2021
DOI: 10.1108/ijshe-10-2020-0406
|View full text |Cite
|
Sign up to set email alerts
|

Lean practices toward a balanced sustainability in higher education institutions: a Brazilian experience

Abstract: Purpose As few studies have explored the causal relationship between both the triple bottom line (TBL) of sustainability and the lean practices in higher education institutions (HEIs), the purpose of this paper is to analyze the relationships between lean practices and sustainable practices in Brazilian HEIs. Design/methodology/approach A survey was conducted with 454 public and private HEIs workers in Brazil. Confirmatory factor analysis and structural equations modeling were used for data analysis. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 80 publications
(120 reference statements)
0
30
0
Order By: Relevance
“…Both management systems take the customer as a basis to improve processes through continuous improvements procedures and thus make them more “clean,” objective and effective. By mapping processes, the organization can identify value adding activities (and non-value ones), delays, and resources employed in the system (Tiso et al, 2021) what becomes essential to optimize continuous improvements and waste elimination practices (Klein et al, 2021a). These elements interact in the Lean System to the pursued objective of higher quality and valued activities (Al-Aomar & Hussain, 2019; Rodgers & Antony, 2019) generating effectiveness.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Both management systems take the customer as a basis to improve processes through continuous improvements procedures and thus make them more “clean,” objective and effective. By mapping processes, the organization can identify value adding activities (and non-value ones), delays, and resources employed in the system (Tiso et al, 2021) what becomes essential to optimize continuous improvements and waste elimination practices (Klein et al, 2021a). These elements interact in the Lean System to the pursued objective of higher quality and valued activities (Al-Aomar & Hussain, 2019; Rodgers & Antony, 2019) generating effectiveness.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The realization of actions and plans with a long-term focus, even if it leads to financial losses in the short term, is essential because the application of Lean requires changes in culture and in the relationship with all stakeholders, which ends up leading to long-term commitments (Ingelsson & Mårtensson, 2014;Womack et al, 2004). Klein et al (2021a) found in their study that long-term thinking composes a set of Lean practices that influence positively economic practices, which in turn envolve strategies and actions that improve efficiency and effectiveness. Dave (2017) exposes the necessary equilibrium within people, technology, and process, and the integration with suppliers to achieve a trusty and mutual long-term relationship to obtain as a result a stronger process improvement.…”
Section: H2: the Elimination Of Waste Positively Influences Process E...mentioning
confidence: 99%
See 3 more Smart Citations